Pelatihan Budikdamber Sebagai Dukungan Gemarikan Di Desa Pongkai Istiqomah - Chicka Willy Yanti; Era Vazira; Yulis Tio Rini; Richa Nadila Sally; Novi Diana Sari; Benta Sybektianto; Ibe Ibrahim Viari; Nasya Defitri Liana; Leoni Putri Anggraini; Juriant Aryo Gandhi; Riska Irma Septiana (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Training on cultivating fish in buckets is one of the main work programs of KKN village development service activities carried out in Pongkai Istiqomah Village. This program aims to support the people of Pongkai Istiqomah Village in GEMARIKAN (Movement to promote fish eating) and also aims to prevent stunting in Pongkai Istiqomah Village. The target of this budikdamber training is the entire community of Pongkai Istiqomah Village, and the PKK as a partner in the organization which is expected to be a contact person with the community. The problems of partners in Pongkai Istiqomah Village are: Firstly, community activity in the fisheries sector in cultivating fish has not been maximized because it requires quite a large amount of capital, secondly, the community's understanding of the importance of consuming fish has not been maximized. The solution to the partners' problems implemented in this service is to hold a training program for making Fish Cultivation in Buckets. The method used is taking a direct approach with the community, counseling and practice of making Fish Cultivation in Buckets. The outputs resulting from this program are: firstly increasing public knowledge and understanding in catfish cultivation, secondly increasing public understanding of the importance of consuming fish and the importance of preventing stunting.